Generational changes in tobacco use by young women: A cross‐generational analysis of mother–daughter dyads. (5th August 2014) - Betts, Kim S.; Williams, Gail M.; Najman, Jakob M.; Alati, Rosa
Abstract Introduction and Aims Cross‐generational evidence is needed to confirm the decline in young female smoking and to identify factors that impede cessation despite two decades of government intervention. Design and Methods Data are from the Mater University Study of Pregnancy, a cross‐generational pre‐birth cohort study beginning in 1981 in Australia. The sample comprised of 993 mother–daughter dyads, for which mothers were aged 18 ≤ 25 at the baseline measurement and their daughters were between the same ages when assessed 21 years later. We used multinomial logistic regression for clustered data to assess associations between four levels of cross‐generationally measured mothers and daughters smoking in early adulthood, and assessed the role of education and depressive symptoms. Results The rate of smoking had declined substantially in the daughters' generation, with mothers having 5.77 (95% confidence interval 4.24, 8.09) and 2.04 (95% confidence interval 1.60, 2.64) times the odds of smoking at heavy and moderate levels, respectively. Smoking across the two cohorts was found to interact with education and depressive symptoms, such that daughters who did not complete secondary school or who had depressive symptoms were at greater risk of smoking than their mothers were 20 years earlier. Discussion and Conclusions Over two generations of mothers and daughters, smoking prevalence and smoking intensity has declined, largely in line with findings from national surveys. The remaining smoking has concentrated heavily among those who did not complete secondary education, and there is evidence that increases in light smoking among the daughters may be related to depression. [Betts KS, Williams GM, Najman JM, Alati R. Generational changes in tobacco use by young women: A cross‐generational analysis of mother‐daughter dyads. Drug Alcohol Rev 2014;33:540ߝ547]